KETERANGAN SAKSI YANG MENGAKIBATKAN PUTUSAN BEBAS (VRIJSPRAAK) KEPADA TERDAKWA TINDAK PIDANA PEMBUNUHAN DITINJAU DARI ASAS IN DUBIO PRO REO (STUDI PUTUSAN NOMOR : 155/Pid/2020/PT TJK) - Sidauruk, Cancolio Frederick; Hutabarat, Rugun Romaida (Universitas Ekasakti, 2023)
The position and role of the witness in a criminal case is evidence to uncover and dismantle a crime. The judiciary is used to prove a crime, evidence and evidence play a role in the process of proving the Criminal Procedure Code. Witness does not give confidence to the Panel of Judges, so that the Panel of Judges is obliged to give a decision in favor of the accused (in dubio pro reo). The judge's decision is a decision whose contents impose a sentence that already has permanent legal force, so the decision can be executed. One type of judge's decision is an acquittal.